Application of Wireless Sensor Network and GSM Technology: A Remote Home Security System - Arora, Atul; Malik, Ankit (IJRDO -Journal of Computer Science Engineering, 2015)
In this paper, a low-power consumption remote home security alarm system developed by applying WSN and GSM technology is presented. It can detect the theft, leaking of raw gas and fire, and send alarm message remotely. The hardware of this system includes the single chip C5081F310, wireless receiving and sending chip CC1100 as well as the SIMENS TC35 GSM module. The system software developed in C51 language has the ability of collecting, wireless receiving and sending data, and can send a piece of alarm short message to the user’s mobile phone when some dangerous condition has been detected